The Correlation Between Mean Pulmonary Arterial Pressure And NT-proBNP In Adult Patient With Uncorrected Atrial Septal Defect - Jomanzyah MUA., et al (ACI (Acta Cardiologia Indonesiana), 2017)
The Correlation Between Mean Pulmonary Arterial Pressure And NT-proBNP In AdultPatient With Uncorrected Atrial Septal Defect